Tool design for reducing excessive transportation in a textile industry: case study in a textile company in Indonesia - Aji Prasojo; Didik Nurhadiyanto; Gulzhaina K. Kassymova (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
This research aimed to design a tool that can reduce one type of waste on the production floor, namely excessive transportation in the form of a waste of transportation time. The design of the tool was carried out by inspecting to the details of the failures that occurred in the previous means of transportation. This development research implemented stopwatch time study method and failure mode and effect analysis to find out the value of the loss of transportation time and the types of failures that cause it. The sample of the transportation process time was taken by simple random sampling method from the intensity of the transportation process per month, based on the type of transportation process on the production floor of a textile company. Then the design of the tool was carried out using the morphological matrix method and weighted objectives table to create the design that fits the needs. The results show that the prediction of the amount of excessive transportation in the form of a waste of time can be minimized by 8,11 hours. Moreover, the new design tool also has a safe structure due to its attained maximum equivalent stress was 17.4 MPa which was smaller than the maximum yield stress of the ST37 material.